The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1515/dmpt-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of cytochrome P450 enzymes: CYP2C9, CYP2C19, CYP2D6, CYP3A4, and CYP3A5 in the Croatian population

Abstract: The frequency of the CYP allelic variants, genotypes, and predicted phenotypes in the Croatian population is in accordance with the other European populations, between the values of published data for Middle European and Mediterranean populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 60 publications
4
21
2
Order By: Relevance
“…Our findings of the CYP2C19*17 frequency in Kosovars are very similar to reports from the neighbouring countries, Greece (19.61 %, p=0.69) and Macedonia (20.2 %; p=0.84) in particular (23,24,31). In Caucasians its frequency varies from 15.4 % to 20.2 % (17).…”
Section: Cyp2c19supporting
confidence: 88%
See 2 more Smart Citations
“…Our findings of the CYP2C19*17 frequency in Kosovars are very similar to reports from the neighbouring countries, Greece (19.61 %, p=0.69) and Macedonia (20.2 %; p=0.84) in particular (23,24,31). In Caucasians its frequency varies from 15.4 % to 20.2 % (17).…”
Section: Cyp2c19supporting
confidence: 88%
“…This finding corresponds to the other reports for Caucasians (18,24,28), as it varies from 85 to 96 % (38). The CYP3A5*3 allele plays an important role in the pharmacokinetics of tacrolimus (basic therapy for immunosuppression in patients who undergo solid organ and haematopoietic stem cell transplantation) and imatinib (a tyrosine kinase inhibitor, which is the drug of choice in treating blood malignancies such as chronic myeloid leukaemia) (39).…”
Section: Cyp3a5supporting
confidence: 87%
See 1 more Smart Citation
“…Based on previous investigations in the target population , we expected frequency of the variant allele at MDR1/ABCB1 1236C>T to be around 40% and frequency of intermediate or slow CYP2C9 or CYP2C19 metabolizers to be around 20–30%. Since we had no insight into the frequency of variant alleles at other genotyped loci, which might be ethnically specific, we opted not to define the sample size on an a priori power calculation but reasoned that subjects should be enrolled until the smallest treatment‐by‐variant allele carriage subset included at least 10 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…To date, at least 28 alleles of CYP2C19 have been identified, and there are ethnic and geographical differences in the distribution of CYP2C19 variants (Kurose et al, 2012). When compared with Caucasian and African populations, CYP2C19 à 1 allele (wild-type) frequency was significantly lower, while the frequency of CYP2C19 à 3 allele was higher in the Chinese Han subjects (Ganoci et al, 2017;Masimirembwa et al, 1995). Zhou et al (2009) compared allele frequencies of Han samples (Beijing) with five other geographical subpopulations of Han Chinese (Hong Kong, Shanghai, Shantou, Shenyang and Xi'an) and observed that the frequencies of CYP2C19 à 1, à 2 and à 3 were significantly different from that of Shengyang and Xi'an subpopulations.…”
Section: Clopidogrel Metabolism Phenotypementioning
confidence: 99%